Interfacially-grafted single-walled carbon nanotube / poly (vinyl alcohol) composite fibers. (May 2019) - Lee, Won Jun; Clancy, Adam J.; Fernández-Toribio, Juan C.; Anthony, David B.; White, Edward R.; Solano, Eduardo; Leese, Hannah S.; Vilatela, Juan J.; Shaffer, Milo S.P.
Abstract: Nanocomposites are critically influenced by interfacial interactions between the reinforcement and matrix. Polyvinyl alcohol (PVOH) of varying molecular weights were prepared and grafted-to single-walled carbon nanotubes (SWCNTs), to improve the interfacial interaction with a homopolymer PVOH matrix. Nanocomposite fibers were coagulation spun across a broad range of loading fractions, controlled by the spinning dope composition. An intermediate grafted-PVOH molecular weight (10 kDa) maximized grafting ratio, and the final composite mechanical performance; the positive effects were attributed to the increased degree of dispersion of the SWCNTs in the dope, as well as the favorable interface. The PVOH grafting increased the stability of the SWCNT loading fractions (up to 45 wt.%), offering increased strength (up to 1100 MPa) and stiffness (up to 38.5 GPa); at the same time, strain-to-failures remained high (up to 23.3%), resulting in high toughness (up to 125 J g −1 ). Graphical abstract: Image 1